Analisis Seberapa Besar Pengaruh Kemiskinan Laju Jumlah Penduduk dan Inflasi Terhadap Pertumbuhan Ekonomi Indonesia - Muhammad Rafi; Muhammad Mahdor Fauzy; Muhammad Radithya Pratama; Sheila Aprilia Dealova Lumbanraja; Salfiah; Taufiq Ramdhani; Rifky Aulia Nurhandi,; Mohammad Fauzan Darmawan; Deris Desmawan (Mandiri : Jurnal Akuntansi dan Keuangan, 2025)
Everyone wants their country to progress, and a big part of that is economic growth. Basically, economic growth is when a country produces more goods and services over time, which in turn can boost how much income people have on average. It’s like the country’s way of showing that things are getting better—more production, better public services, and so on. For this study, we used numerical data, specifically time series data from 2015 to 2019, analyzed with SPSS. What we found is that there’s a clear link between economic growth and poverty, and also between poverty and how fast the population is growing. Poverty seems to sit right in the middle of these two factors, acting as a kind of bridge. The analysis using Pearson correlation shows that as economic growth goes up, poverty levels tend to go down—that's a major negative relationship. On the other hand, higher poverty is associated with faster population growth, which is a major positive relationship. Interestingly, inflation doesn’t seem to have a big effect on economic growth. This suggests that tackling poverty and managing population growth should be key strategies if Indonesia wants to sustain its economic progress.